Harmoni Komunikasi Pengembangan Masyarakat melalui Peran Praktisi Humas dalam Membangun Citra dan Layanan Publik di Kementerian Agama Kota Salatiga Indonesia - Kharis, Ahmad (Al-I'timad: Jurnal Dakwah dan Pengembangan Masyarakat Islam, 2025)
This study aims to analyze the role of Public Relations (PR) practitioners in enhancing public services and institutional image for community empowerment at the Office of the Ministry of Religious Affairs in Salatiga. The research employs a qualitative approach with a descriptive method. The data sources consist of primary data obtained through interviews with representatives from the Ministry of Religious Affairs in Salatiga and stakeholders related to PR, as well as secondary data derived from social media and the official website of the Ministry of Religious Affairs in Salatiga. Data collection was conducted through observation, interviews, and field documentation. The findings indicate that PR at the Ministry of Religious Affairs in Salatiga plays a strategic role in improving public services, functioning as a communicator, relationship builder, backup management, and good image maker. PR strives to provide the best services with openness and transparency to build public trust in the institution. Additionally, the quality of public services directly contributes to shaping the institution’s image. The key components of image formation perception, cognition, motivation, and attitudes in service enable PR to enhance public satisfaction. Institutional image improvement is further reinforced by the implementation of the "Toleran" slogan (Terbaik, On-time, Lancar, Efektif, Ramah, Akuntabel, Nyaman), which serves as a guideline for service delivery. Thus, the communication strategies implemented by PR play a crucial role in fostering public trust and strengthening the positive image of the Ministry of Religious Affairs in Salatiga.